Local community perceptions of tourism impact in the Bromo Tengger Semeru National Park ecotourism area - Deny Meitasari; Aniesa Samira Bafadhal; Rini Mutisari; Heptari Elita Dewi (Universitas Merdeka Malang, 2023)
Bromo Tengger Semeru National Park (BTSNP) is one of the ecotourism in Indonesia that has been designated by UNESCO as one of the world's biosphere reserve. It is considered to have harmony between ecological and economic aspects. This study aims to analyze local community perceptions of tourism impact at BTSNP ecotourism based on economic, socio-cultural and environmental impacts; and analyze the correlations between the impact of and the demographic characteristics of respondents. The data was obtained from Tengger community in Sapikerep Village, Sukapura Subdistrict, Probolinggo Regency using questionnaire and it was analyzed with descriptive statistic and correlation analysis using Kendall's tau-b test. The results of this study show that the residents’ perceived of the impact of tourism is mostly positive (>80% agreed) towards three aspects of tourism impacts. Then, it was found that residents who own a business in a tourist area had a positive significant correlation with perception of tourism impact from the economic and socio-cultural dimension. As for other demographic characteristics, such as age, gender, income level, and education level, there is no significant correlation with perceived of tourism impacts. The existence of the BTSNP brings opportunities for local residents to become entrepreneurs. Local residents who own a business more likely to have better perception of tourism impact. The positive impact from the economic and socio-cultural side is enjoyed more by the people who are directly involved in tourism activities.